Social Informatics 5th International Conference, SocInfo 2013, Kyoto, Japan, November 25-27, 2013, Proceedings - Jatowt, Adam; Lim, Ee-Peng; Ding, Ying; Miura, Asako; Tetzuka, Taro; Dias, Gael; Tanaka, Katsumi; Flanagin, Andrew; Dai, Bing Tian (Information Systems and Applications, incl. Internet/Web, and HCI, 2013)
This book constitutes the proceedings of the 5th International Conference on Social Informatics, SocInfo 2013, held in Kyoto, Japan, in November 2013. The 23 full papers, 15 short papers and three poster papers included in this volume were carefully reviewed and selected from 103 submissions. The papers present original research work on studying the interplay between socially-centric platforms and social phenomena.